Tuning whispering gallery mode lasing from self-assembled polymer droplets - Ta, Van Duong (2013)
Optical microcavities are important for both fundamental studies of light-matter interaction and applications such as microlasers, optical switches and filters etc... Tunable microresonators, in which resonant modes can be manipulated, are especially fascinating. Here we demonstrate a unique approach to mechanically tuning microresonators formed by polymer droplets with varying sizes. The droplets are self-assembly inside an elastic medium. By incorporating different dye molecules into the droplets, optically pumped lasing with selective wavelengths in a range of about 100 nm are achieved. Lasing action is ascribed to whispering gallery modes, verified by rigorous characterizations. Single longitudinal mode lasing is obtained when the droplet diameter is reduced to about 14 μm. Tuning lasing modes are clearly demonstrated by mechanical deformation. Our finding provides an excellent platform for exploring flexible and tunable microlasers for plastic optoelectronic devices.